Implementasi Sistem Informasi Logistik Barang Masuk dan Keluar Berbasis Web untuk Efisiensi Operasional di BPBD Kabupaten Kudus - Rhenal Verdinand; R.Rhoedy Setiawan (Al-DYAS, 2026)
This community service activity was motivated by the importance of logistics management at the Regional Disaster Management Agency (BPBD) of Kudus Regency in supporting disaster preparedness and response, while the recording and reporting processes that were still carried out manually caused delays in information, data inaccuracies, and difficulties in monitoring stock availability in real time. This activity aimed to implement a web-based logistics information system to improve the efficiency, accuracy, and transparency of logistics management at the BPBD of Kudus Regency. The implementation method included needs analysis through observation and interviews, system design and development, functional testing, as well as user training and assistance. The results of the activity showed that the developed system was able to facilitate the computerized recording of incoming and outgoing goods, provide real-time stock information, and generate logistics reports automatically. The system implementation was proven to reduce recording errors, accelerate the reporting process, and improve operational efficiency. These findings indicate that the digitalization of logistics management provides practical benefits for the BPBD in supporting faster and more accurate decision-making and has the potential to serve as a model for implementing web-based logistics systems in other regional disaster management agencies.